2022
DOI: 10.1186/s12891-022-05717-8
|View full text |Cite
|
Sign up to set email alerts
|

Blood titanium levels in patients with large and sliding titanium implants

Abstract: Background Titanium, which is known to be a highly biologically inert element, is one of the most commonly used metals in orthopaedic implants. While cobalt and chromium blood metal ion testing is routinely used in the clinical monitoring of patients with metal-on-metal hip implants, much less is known about the levels of titanium in patients with other implant types. The aim of this study was to better understand the normal ranges of blood titanium levels in patients implanted with large and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…21 Serum titanium levels are likely associated with the duration of treatment. Tognini et al 25 reported a median serum titanium level of 9.7 ppb in patients with MCGR at a median follow-up of 30 months. Their patients had a longer follow-up than our cohort and they had higher serum titanium levels.…”
Section: Discussionmentioning
confidence: 99%
“…21 Serum titanium levels are likely associated with the duration of treatment. Tognini et al 25 reported a median serum titanium level of 9.7 ppb in patients with MCGR at a median follow-up of 30 months. Their patients had a longer follow-up than our cohort and they had higher serum titanium levels.…”
Section: Discussionmentioning
confidence: 99%
“…1,3 Titanium and its alloys are among the metallic materials and are widely used in implantology. 4 This is not only due to the fact that the chemical compositions of these materials are very diverse, which allows for their appropriate selection in terms of possible allergic reactions. 1 Crucial are their biocompatibility, biomechanical properties and good corrosion resistance (Table 1), which is a consequence of the formation of a stable passive layer on the titanium surface.…”
Section: Introductionmentioning
confidence: 99%
“…Titanium and its alloys are among the metallic materials and are widely used in implantology 4 . This is not only due to the fact that the chemical compositions of these materials are very diverse, which allows for their appropriate selection in terms of possible allergic reactions 1 .…”
Section: Introductionmentioning
confidence: 99%